THE ROLE OF BHABINKAMTIBMAS IN ANTICEPING THE SYMPTOMS OF RADICALISM IN COMMUNITY EMPOWERMENT TO REALIZE INTERRELIGIOUS HONOR IN THE CITY OF BANDAR LAMPUNG - Edwin, Edwin; Basyar, Syarifudin; Yanti, Fitri; Saputra, Renaldi Eka (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The growth of religious thought with a radical character has developed rapidly in Indonesia and has become a serious threat to religious harmony. The purpose of this study is to find out and analyze how the role of Bhabinkamtibmas is active, passive and participatory in anticipating radicalism symptoms in community empowerment in order to create inter-religious harmony in the city of Bandar Lampung. This research method is descriptive qualitative which collects primary and secondary data by means of observation, interviews and documentation. Then the role of Bhabinkamibmas is the spearhead of the police at the lower level with 3 functions, namely an active role, a passive role and a participatory role.